Il post-costruttivismo, o l’Art Déco sovietica - Kristina Krasnyanskaya (eSamizdat)
This article sheds light on the phenomenon called 'Soviet design', specifically the quasi-style that arose under the influence of its American version – 'Soviet Art Deco'. The term 'Soviet Art Deco' in relation to Soviet art and architecture is still discussed by contemporary Russian experts and art historians. However, the expansion of knowledge about artistic processes in the USSR of the 1930s makes it possible to draw a conclusion about the continuity and unidirectionality with the artistic phenomena happening around the world in architecture, cinema, decorative and applied art. The author of this article traces the interrelationships and influence of global processes in the style formation in architecture and interiors of the Soviet period. Soviet architects', artists' and sculptors' contact with American and European colleagues, participation in international exhibitions, travel abroad and exchange of professional experience influenced their work. Soviet architecture and art has its own special version of one of the most grandiose, eclectic and popular styles of the 20th century.